2002
DOI: 10.1111/j.1571-9979.2002.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Long‐Term Impact of a Community Conflict Resolution Process: A Case Study Using Content Analysis of Public Documents

Abstract: What are the enduring effects of community‐based conflict resolution processes? According to the research reported here, lessons participants learn in conflict resolution processes disseminate to their communities; secondly, such dissemination can be measured by content analysis of participants’ constituent organization newsletters. The authors illustrate their findings with a case study of the New Community Meeting conflict resolution model (NCM), implemented 1997–98 in an Oregon community to address business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Accordino, Galster, and Tatian (2005) demonstrated that targeted public and nonprofit investment in seven neighborhoods in Richmond, Virginia, triggered a reinvestment of private capital after years of decline, compared to estimated increases in housing values based on 5 years of data on citywide and nearby housing investments and home prices. Gwartney, Fessenden, and Landt (2002) reported positive results in an evaluation of community conflict resolution programs, which aimed toward community-wide change in attitudes and practices in handling conflict; a systematic scan of community-based publications revealed a marked community-wide increase in conflict resolution perspectives, language, and actions from a pre-intervention baseline. No other plausible explanation or confounding program influences were present during this timeframe.…”
Section: Evaluators Of the Jobs-plus Community Revitalization Initiative For Public Housingmentioning
confidence: 99%
“…Accordino, Galster, and Tatian (2005) demonstrated that targeted public and nonprofit investment in seven neighborhoods in Richmond, Virginia, triggered a reinvestment of private capital after years of decline, compared to estimated increases in housing values based on 5 years of data on citywide and nearby housing investments and home prices. Gwartney, Fessenden, and Landt (2002) reported positive results in an evaluation of community conflict resolution programs, which aimed toward community-wide change in attitudes and practices in handling conflict; a systematic scan of community-based publications revealed a marked community-wide increase in conflict resolution perspectives, language, and actions from a pre-intervention baseline. No other plausible explanation or confounding program influences were present during this timeframe.…”
Section: Evaluators Of the Jobs-plus Community Revitalization Initiative For Public Housingmentioning
confidence: 99%